Language abilities and phonological information processing mediate the association of spelling with bilingualism and socioeconomic status - Schöfl, Martin; Weber, Christoph; Steinmair, Gabriele; Zepnik, Sabine; Grimm, Angela (Frontiers in Education, 2024)
Introduction Research to date has focused on the associations between spelling and (i) its precursors (phonological information processing and language) and (ii) socioeconomic status and bilingualism. Studies have also indicated that bilingualism and parental education are associated with spelling precursors. Whereas these associations have previously been analyzed individually, this study proposes a mediation model in which the effects of socioeconomic status and bilingualism on spelling are mediated by phonological information processing and language skills. Methods A total of 1,012 German-speaking first graders attending primary schools in Austria were assessed at the beginning of the first grade on their phonological information processing and language abilities, and their spelling abilities were tested again at the end of the first grade. Subsequently, a structural equation modeling approach was employed to evaluate the mediation model. Results In line with the mediation hypothesis, the results show indirect effects of parental education (as a measure of socioeconomic status) on spelling via language and phonological information processing. In addition to mediation, we also found a direct effect of SES on spelling performances. For bilingualism, the results support full mediation as an indirect effect via language abilities. Notably, we found no effect of bilingual status on phonological information processing. Discussion This study highlights the ongoing need for systematic oral language training for bilingual children and children from low-SES backgrounds that starts in preschool and continues throughout primary school. Moreover, given the predictive effect of phonological awareness on spelling achievement, phonological awareness should be part of the training for preschool and school-aged children.